Neurofeedback Training for Psychiatric Disorders Associated with Criminal Offending: A Review - Fielenbach, Sandra; Donkers, Franc C. L.; Spreen, Marinus; Visser, Harmke A.; Bogaerts, Stefan (Frontiers in Psychiatry, 2018)
Background Effective treatment interventions for criminal offenders are necessary to reduce risk of criminal recidivism. Evidence about deviant EEG-frequencies underlying disorders found in criminal offenders is accumulating. Yet, treatment modalities such as neurofeedback are rarely applied in the forensic psychiatric domain. Since offenders usually have multiple disorders, difficulties adhering to long-term treatment modalities, and are highly vulnerable for psychiatric decompensation, more information about neurofeedback training protocols, number of sessions, and expected symptom reduction is necessary before it can be successfully used in offender populations. Method Studies were analyzed that used neurofeedback in adult criminal offenders, and in disorders these patients present with. Specifically aggression, violence, recidivism, offending, psychopathy, schizophrenia, ADHD, substance use disorder, and cluster B personality disorders were included. Only studies that reported changes in EEG-frequencies post-treatment (increase/decrease/no change in EEG amplitude/power) were included. Results Databases Psychinfo and Pubmed were searched in the period 1990-2017 according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), resulting in a total of 10 studies. Studies in which neurofeedback was applied in ADHD (N=3), substance use disorder (N=3), schizophrenia (N=3) and psychopathy (N=1) could be identified. No studies could be identified for neurofeedback applied in cluster B personality disorders, aggression, violence or recidivism in criminal offenders. For all treatment populations and neurofeedback protocols, number of sessions varied greatly. Changes in behavioral levels ranged from no improvements to significant symptom reduction after neurofeedback training. The results are also mixed concerning post-treatment changes in targeted EEG-frequency bands. Only three studies established criteria for EEG-learning. Conclusions Implications of the results for the applicability of neurofeedback training in criminal offender populations are discussed. More research focusing on neurofeedback and learning of cortical activity regulation is needed in populations with externalizing behaviors associated with violence and criminal behavior, as well as multiple comorbidities. At this point, it is unclear whether standard neurofeedback training protocols can be applied in offender populations, or whether QEEG-guided neurofeedback is a better choice. Given the special context in which the studies are executed, clinical trials, as well as single-case experimental designs, might be more feasible than large double-blind randomized controls.